Ultrasonographic Validation for Needle Placement in the Tibialis Posterior Muscle - Stephanie R. Albin; Larisa R. Hoffman; Cameron W. MacDonald; Micah Boriack; Lauren Heyn; Kaleb Schuler; Annika Taylor; Jennie Walker; Shane L. Koppenhaver; Mark F. Reinking (International Journal of Sports Physical Therapy)
# Background